ANALYSIS OF MODERN REQUIREMENTS FOR THE LEVEL OF FOREIGN LANGUAGE PROFICIENCY OF ENGINEERING SPECIALISTS - K. M. Inozemtseva (Obrazovanie i Nauka, 2017)
Introduction. At present, in Russian higher professional education we can observe a shift to the new educational paradigm based on Professional Standards (PS). According to the Federal Law of 02.05.2015 № 122 «About amendments to the Labour Code of Russian Federation and the articles 11 and 73 of «The Law on Education in Russian Federation» formation of the Federal State Educational Standards of Higher Education requirements for expected learning outcomes on universities’ main educational programs is implemented on the basis of relevant Professional Standards. This causes necessity of work on conjunction of Professional Standards, Federal State Educational Standards and universities’ main educational programs.The aim of this article is to demonstrate the influence of a new educational paradigm on the choice of contents, technologies and activities used in foreign language teaching at Russian technical universities.Methodology and research methods. The research methodology is based on the concept of diversification of engineers’ continuous professional foreign language training (T. Yu. Polyakova). In view of priority value of PS for developing universities’ main educational programs the updating of the above concept needs thorough analysis of both PS requirements for the level of foreign language proficiency of engineering specialists and study of scientific literature on the above problem.Results. This research results in interpretation and clarification of generalized PS requirements for the actual needs of industries and individuals in foreign language proficiency. The research also causes Language for Specific Purposes (LSP) program developers’ and LSP teachers’ pedagogical reflection about their readiness to form foreign language (FL) professional communicative competence of an engineer. It is concluded that a teacher needs to consider axiological aspects of engineering activity in order to understand the nature of the work performed by the engineer; to be able to select the corresponding content, educational technologies and types of educational activity integrating a foreign language and specialty. For this purpose the teacher needs fundamental preparation in the field of theoretical-methodological foundations of interdisciplinary approach in FL education, practice of the subject-integrated FL training, and also readiness for continuous professional development.Scientific novelty. The research helps to interpret requirements of recently developed and implemented engineering PS as applied to FL training at technical universities. It also contributes to the fundamental work on harmonization of Professional Standards, Federal State Educational Standards and university educational programs.Practical significance. The research assists new FL programs’ developers who face with difficulties in transfer of «labour functions», for which FL proficiency is necessary, to the competences being formed in the FL classes. It also helps to choose appropriate educational technologies for effective interdisciplinary FL teaching.